2022
DOI: 10.1159/000520266
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy in Patients with Chronic Kidney Disease: A Systematic Review

Abstract: <b><i>Background:</i></b> Renal calculi in chronic kidney disease (CKD) are not uncommon. Percutaneous nephrolithotomy (PCNL) is a standard treatment for large renal calculi. PCNL in CKD has been a subject of debate as it may improve the renal function with stone clearance but may be associated with an increased complication rate. Studying the impact of PCNL in CKD patients is of utmost significance. <b><i>Objective:</i></b> The aim of the study was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The patients were further divided into CKD3 and CKD4 subgroups, and the differences in postoperative complication rates were comparable. The overall post-PCNL complication rate in our study was 32.8%, which is in accordance with the results of Mehra K [4], who reported that the overall complication rate of PCNL in patients with renal insu ciency was 31.9%, and all the complications were manageable.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The patients were further divided into CKD3 and CKD4 subgroups, and the differences in postoperative complication rates were comparable. The overall post-PCNL complication rate in our study was 32.8%, which is in accordance with the results of Mehra K [4], who reported that the overall complication rate of PCNL in patients with renal insu ciency was 31.9%, and all the complications were manageable.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that renal dysfunction is associated with a greater risk of perioperative blood transfusion, which is attributed to pathophysiologic characteristics such as platelet-vessel wall dysfunction and poorer coagulation function in patients with renal insu ciency [20]. The blood transfusion rate of PCNL in patients with chronic kidney disease was 12.8%, which was higher than that in the cohort of patients with normal renal function, in whom it is reported to be approximately 7% [4,21]. In our study, SPCNL clearly had a disadvantage in terms of transfusion, which is similar to the ndings of the prospective study reported by Güler et al (MPCNL: 2.0%, SPCNL: 15.2%, P = 0.018) [22].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations